UNVEILING TEMPORAL DYNAMICS: ANALYSIS OF SEMANTIC RELATIVES TENSE IN "EVERYTHING EVERYWHERE ALL AT ONCE" DIALOGUES - Alya Hafizah; Grace Lorise; Syifa Nadiah Khansa (PHILOLOGY Journal of English Language and Literature, 2023)
This article analyzes the usage of semantic relative tense in the dialogue of the movie "Everything Everywhere All at Once" using a condensed descriptive qualitative analysis method. The focus of the analysis is on identifying and interpreting how tense variations impact the story's structure, the character's development, and the movie's themes. This methodology aims to reveal the temporal relationships, changes in meaning, and the overall effect of tense on the storytelling by closely examining the dialogues. This study offers helpful insights into the inventive use of tense in shaping the film's narrative and enhancing its cinematic experience through a systematic analysis of the dialogues.In the “Everything Everywhere All at Once” the dialogues uses present progressive tense for a confirmation from one character to another character, present tense to convey state in the present situation, past progressive tense to express ongoing hope or expectation in the past, and other tenses is used in this movie.